Portraiting the Implementation of Project Based Learning in Teaching Narrative Text for EFL Students with Personality Traits: Introversion and Extroversion - Jumbuh Prabowo; Dwi Rukmini; Mursid Saleh; Rudi Hartono (International Conference on Science, Education, and Technology, 2021)
Writing is still considered as the hardest skill in learning a language. It is because of its complexity. Students must consider writing elements when they express their thought and idea in written form. This research aimed at describing the students writing activities done by implementing Project Based Learning (PjBL). PjBL could encourage student motivation and develop learner autonomy. They also had opportunities for authentic meaningful language use. The data was taken by observing and recording students’ activities in teaching learning process. There were 40 participants from one class of the fourth semester students of English Department who attended Genre Based Writing class taken by using purposive sampling. The research was conducted at English department of University of Sultan Ageng Tirtayasa, Banten. The main outcome of this research was to describe the implementation of Project Based Learning in teaching narrative text. The result showed that through PjBL, both introvert and extrovert students could engage and discuss interactively. Consequently, the activities done before writing have an important role to make students more active and creative in triggering students’ idea to express in written form.